Efficacy of Dr. SKS hair booster serum for the treatment of hair loss in COVID-19 induced persistent telogen effluvium - Khare, Stuti (International Journal of Research in Medical Sciences, 2024)
Background: Excessive hair shedding occurs in patients with coronavirus disease 2019 induced telogen effluvium. Dr. SKS hair booster serum has demonstrated encouraging benefits in different types of alopecia in previous studies. We sought to evaluate the efficacy of Dr. SKS hair booster serum for the treatment of COVID-19 induced persistent TE. Methods: A total of 500 patients aged 18 to 60 years who had recovered from reverse transcription-polymerase chain reaction proven COVID-19 infection but experienced sustained hair fall even after 6 months were included in the study. One millilitre of Dr. SKS hair booster serum injection was administered intradermally in scalp per session. Efficacy and safety outcomes were evaluated at baseline, 3 and 6 months after the treatment. Results: Approximately half of the patients demonstrated excellent improvement in expert panel global photographic assessment at 3 months (vertex area; 43.6% and frontal area; 46%) that was increased at 6 months (vertex area; 48% and frontal area; 50%). Each patient’s clinical condition improved. All patients were satisfied with the results in terms of mean total hair growth satisfaction scale score of five aspects at 3 and 6 months treatment. Conclusions: Intradermal injection of Dr. SKS hair booster serum proves to be effective treatment for hair loss in COVID-19-induced persistent TE.